2019
DOI: 10.1083/jcb.201902101
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensing during directed cell migration requires dynamic actin polymerization at focal adhesions

Abstract: The mechanical properties of a cell’s microenvironment influence many aspects of cellular behavior, including cell migration. Durotaxis, the migration toward increasing matrix stiffness, has been implicated in processes ranging from development to cancer. During durotaxis, mechanical stimulation by matrix rigidity leads to directed migration. Studies suggest that cells sense mechanical stimuli, or mechanosense, through the acto-myosin cytoskeleton at focal adhesions (FAs); however, FA actin cytoskeletal remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 64 publications
5
54
0
Order By: Relevance
“…This clearly illustrates the positive regulatory function of Ena/VASP family members in adhesion formation and exertion of traction forces onto the substratum. The particularly important role of Evl in integrin-dependent adhesion is consistent with very recent work showing its specific requirement for FA maturation, cell-matrix adhesion and mechanosensing (Puleo et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This clearly illustrates the positive regulatory function of Ena/VASP family members in adhesion formation and exertion of traction forces onto the substratum. The particularly important role of Evl in integrin-dependent adhesion is consistent with very recent work showing its specific requirement for FA maturation, cell-matrix adhesion and mechanosensing (Puleo et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Finally, although Ena/VASP proteins are prominent FA components, their roles in cell substrate adhesion and FA formation have also remained controversial. Both inhibitory (Galler et al, 2006) and stimulatory roles (Gupton et al, 2012; Kang et al, 2010; Puleo et al, 2019; Young and Higgs, 2018) on adhesion were reported, whereas one study did not detect any effect in fibroblasts lacking Mena and VASP (Bear et al, 2000). To resolve these discrepancies, we characterized cells disrupted for individual, two or all three Ena/VASP family members in distinct types of parental cells, and explored the impact of their individual and collective removal on formation of different protrusion types, migration efficiency and adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…In extension, the reaction to chemotactic (biochemical) stimulation is amplified in cells with decreased EVL expression, indicating that EVL uniquely facilitates the reaction to mechanical stimuli. A scheme is put forward in which EVL-driven FA actin polymerization strengthens FAs while mechanically paced, which thereby improves mechanosensors, mechanically oriented motility and durotaxis (Puleo et al, 2019).…”
Section: Mechanical Cues Induce Directed Motilitymentioning
confidence: 99%
“…Apart from actin filament polymerization based protrusive forces, it has been hypothesized that the suppression of myosin contractility has an impact on the directionality of cell movement (Puleo et al, 2019). There is an upregulation of genes/proteins such as Ubiquitin domain−containing protein 1 (UBTD 1) that interact with E2 enzymes of the ubiquitin-proteasome system due to environmental cues, such as stiff matrices (Torrino et al, 2019).…”
Section: Cytoskeletal Mechanicsmentioning
confidence: 99%
“…First, we screened a panel of breast cancer cell lines and patient-derived xenograft (PDX) primary cells for mechanoresponse in the relevant range for breast tumors 10 , using stiffnesstuned, collagen-coated hydrogels that were either 0.5 kPa (soft) or 8.0 kPa (stiff), and employing well-established mechanosensing and mechanotransduction readouts (differential cell spreading and CTGF gene expression, respectively) 1,14 . While all of the cells tested showed elevated mechanoresponse on stiff hydrogels compared to soft, SUM159 cells showed the greatest combined response (Fig.1b).…”
mentioning
confidence: 99%